Pelatihan Berbicara Bahasa Inggris bagi Santri di Pakisaji, Kab. Malang - Indah Nur'Aini; Puspita Dyah Tri Utami; Lala Nurin Naima (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The ability to speak English has become a popular issue in the management of foundation to be learned that Islamic boarding school students need English speaking training activities to improve their communication skills in foreign languages. Based on observations, the students have different basic abilities so it was decided to provide basic language training. This training was attended by 19 students consisting of 8 male students and 11 female students and carried out five stages including field assessment, preparation, program planning, implementation, and evaluation. This training uses an educational and mentoring approach. It was found that 63.15% of the students experienced an increase in their English-speaking skills and 36.84% less. This is due to two inhibiting factors, namely time and discipline. So, it is recommended that the next training activities be carried out regularly and participants are committed to learning and the board of Islamic boarding schools or foundations are more involved in the English language learning program.